The Impact of Farming Methods on Dairy Cow Milk Output on Tiny-Scale Farms: An Analysis - Neeraj Das, Bhawna Wadhwa, Jayashree M kudari (Revista Electronica de Veterinaria, 2024)
Dairy cow milk is a nourishing beverage produced from the lactating milk of breastfeeding cows and is recognized for having essential elements, including vitamins, calcium, and protein. It is the leading supplier of dairy products, supporting human nutrition and a wide range of culinary uses around the globe. Numerous dairy management strategies (DMSs) have been developed in response to the significant interest in the issue of raising milk yields (MYs) among tiny-scale dairy cow farmers (SDCFs). Adoption of these DMSs has yet to enhance MYs on-farm, and DMS performance varies among farms. This analysis generates data from several locations to examine the effects of different methods of farming on the milk production of dairy cows in small-scale farms. A comprehensive understanding of the patterns and trends in dairy cow milk data is accessible through the analysis of the data on the Enhanced Genetic Gains (EGP) initiatives 2016–2019. Climate problems, breeding and genetics, and feeding habits are significant factors that affect the yield of dairy cow milk at small-scale farms. The chi-square test is the statistical analysis technique used to evaluate the relationship or independence of specific variables in a dataset. Finally, a comprehensive analysis of the production of dairy cow milk on small-scale farms demonstrates the complex interactions among farming techniques, environmental conditions, and total productivity. Our outcomes imply that the most effective way to raise MYs on farms is to combine better feeding practices with better cow breeds.